The use of ex-vivo normothermic perfusion for the resuscitation and assessment of human kidneys discarded because of inadequate in situ perfusion. Issue 1 (December 2015) - Hosgood, Sarah; Barlow, A.; Dormer, J.; Nicholson, M.
Abstract Background Many kidneys are rejected for transplantation due to inadequate in situ perfusion during organ retrieval because of the risk of additional ischaemic injury and microvasculature thrombosis. This study describes the use of ex vivo normothermic perfusion (EVNP) for the resuscitation and assessment of human kidneys that were discarded after inadequate in situ perfusion. Methods Twenty-two human kidneys were retrieved but then deemed unsuitable for transplantation, primarily due to inadequate in situ perfusion. After a period of static cold storage, kidneys were perfused for 60 min with an oxygenated red cell based solution at 36 °C. Results Nineteen out of 22 kidneys (86 %) were from DCD donors. During EVNP, kidneys were assessed and scored based on their macroscopic appearance, measures of renal blood flow and urine production. Kidneys were scored from 1 indicating the least injury to 5, indicating the worst. Twelve kidneys had an EVNP score of 1–2, 7 scored 3–4 and 3 kidneys scored 5. The EVNP score 5 kidneys had a low level of tubular function compared to the score 1–4 kidneys. Their perfusion parameters did not improve during EVNP and they were considered non-transplantable. There was no association between the histological evaluation and EVNP parameters. Conclusion EVNP restores function ex vivo and enables an assessment of kidneys that have been declined for transplantation due to inadequate in situ perfusion.